Modulation of natural killer cell exhaustion in the lungs: the key components from lung microenvironment and lung tumor microenvironment - Zhang, Hongxia; Wang, Jian; Li, Fengqi (Frontiers in Immunology, 2023)
Lung cancer is the leading cause of tumor-induced death worldwide and remains a primary global health concern. In homeostasis, due to its unique structure and physiological function, the lung microenvironment is in a state of immune tolerance and suppression, which is beneficial to tumor development and metastasis. The lung tumor microenvironment is a more complex system that further enhances the immunosuppressive features in the lungs. NK cells are abundantly located in the lungs and play crucial roles in lung tumor surveillance and antitumor immunity. However, the immunosuppressive microenvironment promotes significant challenges to NK cell features, leading to their hypofunction, exhaustion, and compromised antitumor activity. Thus, understanding the complex interactions among the lung microenvironment, lung tumor microenvironment, and NK cell exhaustion is critical for the development of effective cancer immunotherapeutic strategies. The present review will discuss NK cell hypofunction and exhaustion within the lung microenvironment and lung tumor microenvironment, focusing on lung tissue-specific factors, including key cytokines and unique environmental components, that modulate NK cell activation and function. Understanding the functional mechanisms of key factors would help to design strategies to reverse NK cell exhaustion and restore their antitumor function within the lung tumor microenvironment.